Dynamic evolution of bone marrow adipocyte in B cell acute lymphoblastic leukemia: insights from diagnosis to post-chemotherapy - Xi Jia; Naying Liao; Yunqian Yao; Xutao Guo; Kai Chen; Pengcheng Shi (Cancer Biology & Therapy)
Adipocyte is a unique and versatile component of bone marrow microenvironment (BMM). However, the dynamic evolution of Bone Marrow (BM) adipocytes from the diagnosis of B cell Acute Lymphoblastic Leukemia (B-ALL) to the post-treatment state, and how they affect the progression of leukemia, remains inadequately explicated. Primary patient-derived xenograft models (PDXs) and stromal cell co-culture system are employed in this study. We show that the dynamic evolution of BM adipocytes from initial diagnosis of B-ALL to the post-chemotherapy phase, transitioning from cellular depletion in the initial leukemia niche to a fully restored state upon remission. Increased BM adipocytes retards engraftment of B-ALL cells in PDX models and inhibits cells growth of B-ALL in vitro. Mechanistically, the proliferation arrest of B-ALL cells in the context of adipocytes-enrichment niche, might attribute to the presence of adiponectin secreted by adipocytes themselves and the absence of cytokines secreted by mesenchymal stem cell (MSCs). In summary, our findings offer a novel perspective for further in-depth understanding of the dynamic balance between BMM and B-ALL.